Interrelatedness, Dynamic Factor Adjustment Patterns and Firm Heterogeneity in Austrian Manufacturing - Sandra Martina Leitner (Johannes Kepler University of Linz, Department of Economics, 2008)
The aim of this paper is twofold: one, it analyzes the dynamic factor adjustment patterns and performance changes of firms in response to periods of rapid adjustment of capital, labor, production and non-production labor; and, two, it sheds light on the role of firm characteristics on the probability of any input spike occurring. Firm-group information incorporated in the Austrian Industry Statistics Survey provides the empirical platform for the analysis. The analysis shows that all input factors considered represent strategic complements and, in the light of skill-technology complements, it proves the absence of any skill bias to the adoption of leadingedge technologies embodied in new machinery and equipment. Furthermore, there is evidence of significant temporary disruptive effects of input spikes on labor productivity and profitability. Non-negligible firm heterogeneity also prevails in Austrian Manufacturing with larger firm-groups and firm-groups facing lower average personnel costs being more likely to experience any input spike. And the strongly regulated labor market in Austria appears to favor non-production workers.
Keywords: 330; Wirtschaftsindikator; Industriestruktur; Investition; Branchenentwicklung; Verarbeitendes Gewerbe; Schätzung; Österreich